Diagnosis and Prognosis of the Hearing Impairment Risk - Gabriel-Dragoş Vasilescu (The Global Environmental Engineers, 2014)
This paper describes a methodological approach on the analysis and on the statistical and probabilistic assessment of the hearing impairment risk, based on the hazards quantified as risk predictors, in order to establish the modalities for assessing the caution limits related to the acceptability ranges. The research has been achieved within the PN 45 07 01 15 project in the framework of the NUCLEU/2009-2010 program. The statistical approach is based on the rational quantification of what exists and can be observed, the probabilistic part of this fact representing the extrapolation to what it can be reasonably deduced from these statistics of hearing impairment occurrence probability. This project has a national and international interest, entailing the increase of occupational health and safety level and ensuring sustainable environmental quality and comfort at workplaces.